A green Christmas! - O'Ryan, Ray (O'Ryan, Ray. Galaxy Zack, 2013)
When a cosmic storm hits, stranding the Nelsons on their new home planet, Nebulon, Zack's hopes of a white Christmas in Vermont are dashed, but Nebulon provides a surprising alternative.